2017
DOI: 10.1097/dcr.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Bupivacaine Use in Transversus Abdominis Plane Blocks Reduces Pain and Postoperative Intravenous Opioid Requirement After Colorectal Surgery

Abstract: Attenuated pain scores observed with liposomal bupivacaine use were associated with significantly lower intravenous opioid and ketorolac use, suggesting that liposomal bupivacaine-containing transversus abdominis plane blocks are well aligned with the opioid-reducing goals of many enhanced recovery protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…21,22 Similar outcomes have also been documented in nonorthopedic cases, including hemorrhoidectomy, bunionectomy, and colorectal and retropubic slingplacement surgeries. 16,17,23,24 Despite these findings, the local anesthetic's effectiveness in reducing postoperative pain and opioid use in spine surgeries has not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Similar outcomes have also been documented in nonorthopedic cases, including hemorrhoidectomy, bunionectomy, and colorectal and retropubic slingplacement surgeries. 16,17,23,24 Despite these findings, the local anesthetic's effectiveness in reducing postoperative pain and opioid use in spine surgeries has not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to decreased inhalant dosing, the need for rescue analgesia, including opioids, is decreased with the use of local/regional analgesia. In humans (Bergese et al, 2012;Blanco, Ansari, & Girgis, 2015;Boerboom et al, 2018;Candiotti, 2012;Lombardi, 2014;Malik, Kaye, Belani, & Urman, 2017;Marques et al, 2014;Stokes et al, 2017) and dogs/ cats (Benito et al, 2016;Carpenter et al, 2004;Flecknell, Kirk, Liles, Hayes, & Dark, 1991;Myrna et al, 2010;Perez et al, 2013;Savvas et al, 2008;Wenger, Moens, Jäggin, & Schatzmann, 2005), local anaesthetics significantly decrease the opioid requirements for intraoperative anti-nociception and postoperative analgesia. Using local anaesthetics to decrease opioid use could be very beneficial in both human and veterinary patients, not only because of the desire to reduce potential opioid-mediated adverse effects, such as dysphoria, vomiting and nausea, but also because the availability of potent opioids may be limited due to legislation, production or country/region.…”
mentioning
confidence: 99%
“…We chose to use liposomal bupivacaine, which has a half‐life that is approximately five times longer than conventional bupivacaine . One study found a significant decrease in opioid use and superior pain control persisting up to 36 h after CRS in TAP block protocols using liposomal bupivacaine compared with nonliposomal agents . Interestingly, they observed this reduction in opioid use more in patients undergoing laparoscopic or robotic surgeries than open procedures, possibly due to the larger proportion of visceral pain in open cases that is not covered by TAP block .…”
Section: Discussionmentioning
confidence: 99%